1996
DOI: 10.1063/1.470761
|View full text |Cite
|
Sign up to set email alerts
|

Multispeckle autocorrelation spectroscopy and its application to the investigation of ultraslow dynamical processes

Abstract: We describe a modification of conventional dynamic light scattering (DLS) using a CCD camera as optical area detector. Scattered intensity autocorrelation functions are determined using both ensemble- and time-averaging. Therefore, the new setup allows for much shorter measurement times compared to conventional DLS. Our apparatus has been checked by investigating a dilute dispersion of polystyrene (PS)–microgel lattices in glycerol. The results agree well with DLS measurements using the standard setup. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 9 publications
2
64
0
Order By: Relevance
“…translational or rotational motion of the sample during the measurement, are necessary in order to obtain · · · E [29,[33][34][35]. Similar arguments hold for the role of nonergodicity in standard DLS experiments [47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…translational or rotational motion of the sample during the measurement, are necessary in order to obtain · · · E [29,[33][34][35]. Similar arguments hold for the role of nonergodicity in standard DLS experiments [47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 81%
“…For diluted, nonergodic samples several methods have been applied to properly average the data obtained in DLS experiments [47][48][49][50][51][52][53]. A good comparative review of some of these methods can be found in Refs.…”
Section: Dynamic Light Scattering By Nonergodic Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…roughness) and slow material relaxation processes [1][2][3]. The use of speckle patterns to determine these properties presents an attractive avenue for the precise characterization of surfaces during laser materials processing using the existing sources of energy.…”
Section: Introductionmentioning
confidence: 99%
“…speckle fluctuations on time scales from a fraction of second up to several hours. In the first implementations of these so-called multispeckle approaches [11,12], the far field detection scheme of traditional DLS was used and the intensity correlation function was calculated from…”
Section: Introductionmentioning
confidence: 99%